The Influence of Social Performance and Environmental Performance on Company Financial Performance Empirical Study on Mining Companies Listed on the Indonesian Stock Exchange (Idx) 2020-2022 - Nurhidayah; Wahyuni; Muhammad Nasrun; Amelia (www.amertainstitute.com, 2024)
This study examines the influence of social performance and environmental performance on the financial performance of mining companies listed on the Indonesia Stock Exchange (BEI) during the period 2020-2022. Employing a quantitative research approach, the study uses secondary data from 15 mining companies. The data were analyzed using SPSS 26 for statistical processing and interpretation. The findings reveal that both social performance and environmental performance have a significant positive impact on financial performance when evaluated individually. Companies that actively engage in social initiatives and prioritize environmental sustainability tend to exhibit improved financial outcomes. These results highlight the strategic value of integrating social and environmental considerations into business practices, as they contribute not only to corporate responsibility but also to financial success. The study provides critical insights for stakeholders, emphasizing the importance of social and environmental performance as drivers of sustainable financial growth. This information supports stakeholders in making informed decisions regarding investments and corporate strategies. The research underscores the need for mining companies to strengthen their commitment to social and environmental initiatives to enhance financial performance and stakeholder trust. Future studies could expand the scope by analyzing other industries and incorporating additional variables such as governance and regulatory compliance to enrich the understanding of performance dynamics.